Psychological Distress and Quality of Life in Pediatric Crohn Disease: Impact of Pain and Disease State. Issue 4 (October 2017) - Claar, Robyn Lewis; van Tilburg, Miranda A.L.; Abdullah, Bisher; Langer, Shelby; Sherif, Dalia; Whitehead, William E.; Drossman, Douglas A.; Levy, Rona L.
ABSTRACT: Objectives: For patients with Crohn disease (CD), symptom reporting may not coincide with disease state; patients in remission may continue to report symptoms and pain, whereas other patients may be symptom-free despite a flare. This phenomenon has been documented in adults but only recently assessed in pediatric patients. The present study assessed the role of pain reporting and disease state in pediatric patients with CD in understanding psychological distress and quality of life. Methods: Participants included 116 children and adolescents ages 8 to 18 years with CD who completed self-report questionnaires assessing pain, disease symptoms, depression, anxiety, functional disability, and quality of life. Physicians completed the Pediatric Crohn's Disease Activity Index to assess disease activity (scores ⩽10 = remission, scores >10 = flare). Results: Approximately two thirds of participants reported pain concordant with disease state. For patients in remission, those with pain experienced significantly increased disability and decreased quality of life compared to patients in remission without pain. For patients in a flare, those without pain experienced significantly decreased disability and depressive symptoms, and improved quality of life compared to patients in a flare with pain. Conclusions: For pediatric patients with CD, report of pain, while in remission or a flare, is associated with increased disability and reduced quality of life. Although levels of depression did not differ by disease state, depressive symptoms did differ by pain report (presence or absence) for those in a flare. Pain reporting in CD appears to be associated with both physical and psychological state and should be assessed regardless of disease activity. Abstract : Supplemental Digital Content is available in the text